Transpedikulárna stabilizácia zlomenín hrudnej chrbtice - Božík, Michal; Magala, M; Heger, Tomáš; Matejička, Dušan; Baka, Július; Šimko, Peter (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2014)
PURPOSE OF THE STUDY: Fractures of the thoracic spine involve injury at the levels of Th2 to Th10. Because of pedicle morphology, pedicle screw fixation is a demanding procedure. However, evidence on the reliability and efficiency of this technique has recently been provided by several studies. The aim of this study was to analyse a group of patients with thoracic spine fractures treated by pedicle screw fixation and to evaluate treatment outcomes. MATERIAL AND METHODS: A total number of 33 patients treated by pedicle screw fixation for thoracic spine fractures between January 2007 and December 2011 were enrolled in this retrospective study. The mean age was 39.7 ± 16.7 years. The evaluation included demographic data, mechanism of injury, associated injuries, neurological status, fracture type (AO classification), levels of the fractured vertebrae, injury-surgery interval, type and duration of surgery, type and length of pedicle screw fixation and complications. The position of pedicular screws in relation to the pedicle walls and correction of kyphotic deformity were assessed on post-operative CT scans. RESULT: Of the 33 patients, 24 had associated injuries (72.7%), 22 had thorax injury (66.7%) and 17 had neurological deficit (51.5%). The most frequent spinal fracture type was type B2, 15 (45.5%); followed by type C, nine (33.3%); and type B1, five (15.1%). The mean injury-to-surgery interval was 5.2 ± 4.3 days. The mean operative time was 210 ± 56 min. The most frequently used configuration of pedicle screw fixation involving two segments above and two below the fracture level was used in 20 cases (58.8%). The position of 149 out of 282 pedicle screws (52.8%) was evaluated on post-operative CT scans as follows: 98 % of the pedicle screws were placed in acceptable positions, 76% were placed completely within pedicle borders. The mean pre-operative Cobb angle was 18.7° ± 8.2°, the mean post-operative Cobb angle was 9.3 ± 3.4°. Six intraoperative and three post-operative complications occurred. During follow-up no instrumentation failure or apparent loss of correction was recorded. DISCUSSION: Early stabilisation of thoracic spine fractures reduces the risk of complications, shortens the hospital stay and allows for faster recovery of patients. Early thoracic spine stabilisation is most beneficial in patients with a high ISS (Injury Severity Score). In the case of small-sized pedicles there is the possibility of pedicle screw insertion via an extrapedicular or parapedicular trajectory. Recommended pedicle screw fixation is two levels above and two levels below the fracture level. CONCLUSIONS: Pedicle screw fixation of thoracic spine fractures is a safe therapeutic method with a low risk of complications. It facilitates effective reduction and stable fixation with a low risk of secondary displacement and implant failure. Key words:transpedicular stabilisation, thoracic spine, fracture, pedicle screws.
Keywords: fraktury páteře; dospělí; skóre závažnosti úrazu; Operative Time; Adult; mladý dospělý; Injury Severity Score; peroperační komplikace; lidé; pedikulární šrouby; Thoracic Vertebrae; Pedicle Screws; retrospektivní studie; Young Adult; hrudní obratle; délka operace; vnitřní fixace fraktury; lidé středního věku; Spinal Fractures; Intraoperative Complications; Retrospective Studies; Middle Aged; Fracture Fixation, Internal; Humans